2019
DOI: 10.24059/olj.v13i3.1650
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Retention: A Closer Look at Institutions That Achieve High Course Completion Rates

Abstract: Although online course completion rates are commonly believed to be lower than in other delivery modes, some programs achieve equal or better course completion rates. This issue presents studies that suggest certain practices contribute to student success. Readers are invited to contribute to work-inprogress on key factors for a framework of effective practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In differentiated instruction, which is based on the principles of Universal Design for Learning (UDL), instructors consider students’ learning preferences, past experiences with the subject matter, and current interests to fully engage students with their learning. The application of UDL principles to learning environments has been tied to increased student engagement (Moore and Fetzner ), persistence (Field, Sarver, and Shaw ; Getzel ), and retention (Field, Sarver, and Shaw ; Getzel ; Moore and Fetzner ). In hybrid classrooms, the range of activities, both in class and online, can provide a diverse group of students with learning techniques that are most applicable to their learning preferences and that help keep them engaged throughout a course.…”
Section: Benefits Of Hybrid Teaching and Learningmentioning
confidence: 99%
“…In differentiated instruction, which is based on the principles of Universal Design for Learning (UDL), instructors consider students’ learning preferences, past experiences with the subject matter, and current interests to fully engage students with their learning. The application of UDL principles to learning environments has been tied to increased student engagement (Moore and Fetzner ), persistence (Field, Sarver, and Shaw ; Getzel ), and retention (Field, Sarver, and Shaw ; Getzel ; Moore and Fetzner ). In hybrid classrooms, the range of activities, both in class and online, can provide a diverse group of students with learning techniques that are most applicable to their learning preferences and that help keep them engaged throughout a course.…”
Section: Benefits Of Hybrid Teaching and Learningmentioning
confidence: 99%
“…Earlier studies consistently reported the popular demands of online courses. In the last decade, there was a 100% increase rate of online course enrollments from 2003 to 2007 (Moore & Fetzner, 2009). Of all students enrolled in higher education in 2013, 32% took at least one online course (Allen & Seaman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Completion rates in online courses are historically lower, about 8-14%, than in the traditional face-to-face courses (Xu & Jaggars, 2011a, 2011b. Moore and Fetzner (2009) contended that the completion rates in online classes are claimed to be 10-20% lower than in traditional ones, along with graduation rates for undergraduate degree being only 56%. The completion rates for graduate online courses in business statistics and finance are also similar (Terry, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Lewis (2009) explains that the "paradigm shift" from face-to-face to online learning can be challenging, but if the learner is committed they can master this mode; a sentiment echoed by others (Kahu et al, 2014;Posey and Pintz, 2014;Oman et al, 2012). Universities are encouraged to support a student's transition to online learning by providing access to orientation modules prior to study commencement, creating relationships with course convenors, peer mentors and other students, and responding to the diverse needs of students (Moore and Fetzner, 2010;Milman, 2013;Posey and Pintz, 2014). The University provides many of these support strategies with the intent to facilitate student success with online programs.…”
Section: Discussionmentioning
confidence: 99%